Integrative Analysis of MicroRNA and Gene Interactions for Revealing Candidate Signatures in Prostate Cancer - Wei, Jingchao; Yin, Yinghao; Deng, Qiancheng; Zhou, Jun; Wang, Yong; Yin, Guangming; Yang, Jianfu; Tang, Yuxin (Frontiers in Genetics, 2020)
MicroRNA (miRNA)-gene interactions have been well established to be involved in the progression of almost all types of tumors including prostate cancer, which is one of the most common types of cancers in men. The present study was intended to explore the significantly dysregulated genes and miRNAs and elucidate the potential miRNA-gene regulatory network in prostate cancer. Integrative analysis of prostate cancer and normal prostate transcriptomic data in The Cancer Genome Atlas (TCGA) dataset was conducted leveraging both differential expression analysis and weighted correlation network analysis (WGCNA). 13 genes (RRM2, ORC6, CDC45, CDKN2A, E2F2, MYBL2, CCNB2, PLK1, FOXM1, CDC25C, PKMYT1, GTSE1, CDC20) were speculated to be correlated with prostate cancer based on functional enrichment analyses. MiRNAs targeting these genes were predicted and 8 miRNAs were intersections between those miRNAs and the hub miRNAs obtained from miRNA WGCNA analysis. 3 genes (E2F2, RRM2, PKMYT1) and 4 miRNAs (hsa-mir-17-5p, hsa-mir-20a-5p, hsa-mir-92a-3p, hsamir-93-5p) were key factors according to the interaction network. RRM2 and PKMYT1 were demonstrated to be significantly related with survival. These findings partially elucidate the dysregulations of gene expressions in prostate cancer and efficient manipulations of miRNA-gene interactions in prostate cancer may be exploited as promising therapeutics.